Aplikasi Sistem Informasi Geografis untuk Analisis Potensi Daerah Resapan Air di Kecamatan Buleleng - PARDEDE, RIO PUTRA NUSANTARA; DIBIA, I NYOMAN; WIYANTI, WIYANTI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Application of Geographic Information Systems for Analysis of the Potential of Watersheds in Buleleng District The research was conducted in Buleleng Subdistrict and lasted from December 2019 to April 2020. The purpose of this study was to determine the potential for water catchment in the study area and determine the distribution of potential water catchment in the study area. The method used is a scoring method with parameters used are soil type, land use, slope and rainfall. The results showed that the potential grade of water catchment areas consisted of rather good, moderate, bad, rather bad, and very bad classes. The potential for water infiltration in the study area is dominated by a rather bad class of 2.305,66 ha (49.11%), then followed by a very bad class of 1.130,75 ha (24.08%), a bad class of 1.088,51 ha (23 , 18%), the class is rather good at 112,35 ha (2.39%) and middle class at 56,73 ha (1.20%).